The clock drawing test, mortality, incident cardiovascular events and dementia. (12th June 2014) - Peters, Ruth; Beckett, Nigel; Pereira, Lisa; Poulter, Ruth; Pinto, Elisabete; Ma, Shuping; Dumitrascu, Dan; Barrowdale, Daniel; Butler, Michael; Fletcher, Astrid; Bulpitt, Christopher
<x xml:space="preserve">Abstract</x> Objective The purpose of this study is to examine the association of the clock drawing test (CDT) with incident dementia, cardiovascular events and mortality in very elderly hypertensive patients. Method All participants were hypertensive and aged 80 years and over. The CDT was administered at baseline and annually thereafter. Data on incident cardiovascular, fatal events and dementia were collected over follow‐up. Results There were 3845 participants recruited and followed up for a mean of 2.1 years. Of these, 2701 completed a CDT with 2259 available at baseline. Of this group, 6.6% had a cardiovascular event, 6.1% died, and 10% were diagnosed with dementia. There was no relationship between baseline CDT score and subsequent cardiovascular events or mortality. For incident dementia, the hazard ratio was 0.88 (95% confidence intervals 0.83–0.94) suggesting that better performance on the baseline CDT was associated with a lower risk of dementia. Conclusion These results provide tentative support for the CDT alongside other cognitive screening tools in a hypertensive elderly population. Copyright © 2014 John Wiley & Sons, Ltd.